Categorization via movement: the syntax and semantics of ambos - Medeiros, Alessandro Boechat de; Martins, Adriana Leitão; Damulakis, Gean Nunes (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2021)
In order to explain the syntactic behavior and describe the meaning of the item ambos in Brazilian Portuguese, we propose, assuming the Distributed Morphology framework, (1) that the acategorial root amb- merges, in the syntactic derivation, to a D that moves from inside a full defi nite DP, and this D categorizes the root; (2) that amb-+D merges back to the DP which D was the head of; (3) that the lower copy of D is erased (or becomes invisible) when the derivation reaches LF; (4) that the meaning of the combination of D and amb- is defi ned only if the context provides a unique set of two individuals with the properties defi ned by the plural NP taken by ambos, and introduces a universal quantifi cation over this set.